PENGARUH MODAL USAHA DAN SIKAP KEWIRAUSAHAAN TERHADAP PENDAPATAN USAHA KECIL (MIKRO) DI KAWASAN M. SAID SAMARINDA - Rahmadiawati Devi (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This study aims to determine and analyze the effect of business capital and entrepreneurial attitudes on the income of micro small businesses in M. Said Samarinda. The variables used in this study consisted of independent variables, namely variables of venture capital and entrepreneurial attitudes. While the dependent variable is business income. In this study using quantitative methods, namely definition, quantitative data measurement and objective statistics through scientific calculations derived from samples of traders in the M. Said Samarinda area. The data collection technique used was observation, questionnaires and literature writing. While the analytical tool used is multiple linear regression analysis. The research concludes that business capital (X_1) and entrepreneurial attitude (X_2) simultaneously have a significant effect on income (Y). The regression equation is Y = 0.507 + 1.237 X_1 + -0,364 X_2. The R value (correlation coefficient) obtained is 0.948 and the R Square value (coefficient of determination) is 0.899 or 89.9%. Overall hypothesis testing (F test) shows that the independent variables (independent) together have a significant effect on income. The results of the partial test (t-test) show that business capital has a significant effect on income, while entrepreneurial attitudes have no significant effect on income. The most influential variable is business capital.